Increasing Rate of Human Bone Marrow Mesenchymal Stem Cell Proliferation in the Presence of Silymarin - HR Ahmadi Ashtiani (Journal of Medicinal Plants, 2010)
Background: Mesenchymal stem cells (MSCs), the non-hematopoietic progenitor cells found in various adult tissues are characterized by their ease of isolation and their rapid growth in vitro while maintaining their differentiation potential, allowing for extensive culture expansion to obtain large quantities suitable for therapeutic application. Silymarin has strong antioxidant and anti-inflammatory activities with positive effect on proliferation on some cell types. Objectives: The aim of this study was to find out the optimal condition of silymarin treatments on mesenchymal stem cell growth and multiplication. Methods: Human MSCs in third passage were divided into 12 groups treated by 50, 75, and 100 μg/ml of silymarin for 2, 7 and 14 days. Cell viability was assayed on day 2 using trypan blue exclusion test. The cell proliferation rate in presence of silymarin was determined using a day-response curve for each dose. Results: Viability was 89%, 93%, and 96% for cells treated with 50, 75, and 100µg/ml silymarin, respectively. Cell viability showed significant increase in all treated cells in comparison with the control group (83%). Based on the day- response curve, it was shown that the rate of cell proliferation in treated cells is significantly higher when exposed to silymarin for 2 - 7 days. However, from 7th day to 14th, silymarin exposure lowers hBMSCs proliferation rate compared to control group. Conclusion: Under optimal condition of silymarin exposure time, the rate of MSC proliferation can be stimulated.